1995
DOI: 10.1021/la00008a045
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Characterization and the Effect of Metal Ions on Langmuir-Blodgett Films of Octasubstituted Calix[4]resorcinarenes

Abstract: Calix[4]resorcinarenes octafunctionalized with methyl -acetate (CALES) or methyl a-acetamide (CALAM) have been used to form Langmuir-Blodgett (LB) films on several different substrates. Spectroscopic characterization of these species as solids, solutions, and LB films were carried out using FT-IR, FT-Raman, UV-visible, and fluorescence spectroscopies. Considering the spectroscopic evidence, the conformation of both CALES and CALAM in the LB films was found to be the flattened cone. It has been shown that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 6 publications
4
27
2
Order By: Relevance
“…These results showed that the UV-vis spectra of the calixarenes are highly solvent dependent because the position, intensity and the shape of the absorbance bands of each compound in solution, have varied with changes in solvent and a red shift is commonly observed. Similar work has been found by Moreira et al [32,36] using a calix [4]resorcinarene octafunctionalized with methyl ␣-acetate or methyl ␣-acetamide when deposited as LB films on several different substrates.…”
Section: Isotherm Graphsupporting
confidence: 83%
See 1 more Smart Citation
“…These results showed that the UV-vis spectra of the calixarenes are highly solvent dependent because the position, intensity and the shape of the absorbance bands of each compound in solution, have varied with changes in solvent and a red shift is commonly observed. Similar work has been found by Moreira et al [32,36] using a calix [4]resorcinarene octafunctionalized with methyl ␣-acetate or methyl ␣-acetamide when deposited as LB films on several different substrates.…”
Section: Isotherm Graphsupporting
confidence: 83%
“…2) were obtained at the air-water interface by recording surface pressure as a function of surface area. These measurements were repeated several times using identical and differing volumes of the solution Isotherms of calixarene compounds have been extensively studied using different materials such as calix [8]arenes [29][30][31] and calix [4]resorcinarenes [32,27]. When compared to our results, similar isotherms have been observed for calix [8]arene monolayers at the air-water interface.…”
Section: Isotherm Graphsupporting
confidence: 81%
“…Calix [4]resorcinarenes 3 are of much interest on account of their unusual complexing properties, conformational flexibility, the great variety of ways in which they can be further derivatized, and their easy availability. The prospect of forming multicomponent species involving calix [4]resorcinarenes makes them of interest for molecular recognition, [4][5][6][7][8][9][10] transport across membranes, 11,12 ion channels, 13 self-assembling monolayers at the air-water interface 7,[14][15][16] and on metals. [17][18][19][20][21] Knowledge of the structure and thermal stability of a range of calixarene solvates will lead to a rational choice of solvents suitable for the study of molecular recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Since the interaction of DTCX with the metal surface takes place through the DT group, the aromatic central groups and the tert-butyl upper rim moieties 3,[18][19][20] are placed at a relatively far position from the surface. The short-range effect of SERS 21 accounts for the weakening of bands attributed to the latter group such as that appearing in the solid (Fig.…”
Section: Resultsmentioning
confidence: 99%